Anticipative Measures on Exotic and Zoonotic Diseases for International Trade - Putri NH, Tri Satya (Indonesian Animal Sciences Society, 2004)
The awareness on the advantage of the international trade role for social welfare encourage a number of countries, including Indonesia to establish regional/international economic organisations aiming at building mutual economic strength. Several prominent economic cooporations are ASEAN Free Trade Area (AFTA), Asia Pacific Economic Cooperation (APEC), and General Agreement on Tariffand Trade (GATT). It is expected that through economic integration trade barriers in the form of tariff barriers and non tariff barrier present among the member countries can be reduced or even eliminated, with a result that the trading goods traffic (including livestock and its products), services, and investment among countries in a region can be carried out more smoothly . From the aspect of animal health, the increase in the traffic of livestock and its products will bring risks due to the entry of animal diseases into Indonesian regions. Indonesia that has been stated to be free from 13 out of 15 contagious diseases according to list A and several diseases based on list B of OIE (Office Internationale des Epizootes) needs to anticipate this through policy reorientation by obeying the agreement on Sanitary and Phytosanitary for food safety, and animal and plant health protection. For livestock and its product commodities, the Directorate General of Livestock Production Building has issued a decree number 71/TN.690/Kpts. DJP/Deptan/2000 regarding the import of livestock and its products using a standard procedure. Besides that, it is necessary to carry out risk analysis, harmonisation, transparency, and the same treatment on products from abroad. In order to maintain animal health status, monitoring, surveillance, optimal reporting system, campaign to enhance the society attention, and quarantine action are required. Key words: Exotic and zoonotic diseases, international trade